2022
DOI: 10.52461/ijnms.v1i3.940
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of curcumin loaded ZnO nanoparticles and their in vitro antibacterial activity

Abstract: Nanotechnology is broadly defined as the study and development of the chemical physical and natural properties of materials, devices, and structures that differ from those found on a larger scale, and Nano patents are derived from the Japanese language. Zinc oxide nanoparticles are used in a wide-ranging application, visible light, catalytic actions, ultrasonic, deodorizing, diabetes treatment, cosmetics, lasers, paints, ultraviolet light absorbing constituents, rubber industry, catalytic agent for light flatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that nanoparticles can be used in the administration of a wide range of drugs, including anticancer drugs, antibiotics, and anti-inflammatory drugs. Examples of nanoparticles used in drug delivery include liposomes, dendrimers, and polymer nanoparticles 6 . NPs within range of 10–1000 nm are considered firm NPs or else particulate distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that nanoparticles can be used in the administration of a wide range of drugs, including anticancer drugs, antibiotics, and anti-inflammatory drugs. Examples of nanoparticles used in drug delivery include liposomes, dendrimers, and polymer nanoparticles 6 . NPs within range of 10–1000 nm are considered firm NPs or else particulate distribution.…”
Section: Introductionmentioning
confidence: 99%